Revitalisasi Manajemen Posyandu Remaja Sebagai Upaya Preventif Kejadian Stunting Melalui Media Berbasis Internet of Thing - Dwi Kustriyanti; Sonhaji Sonhaji; Retno Apriliyanti; Fatriana Dwi Aulia; Lutfiatun Nayyiroh; Yulina Anggi Mawar Dani; Bayu Aji (Journal of Community Development, 2025)
Mawar Youth Integrated Service Post (Posrem Mawar) is located in Ngesrebalong Village, Limbangan District, Kendal, Central Java, which is located on the slopes of Mount Ungaran. Posrem in Ngesrepbalong Village contributed 34 (10.86%) stunted children out of a total of 313 cases in Limbangan Kendal District. The teenage problems that arise are early marriage as many as 37 (6%) in 2021 in the age range 15-18 years, 5 (13.5%) men and 32 women (86.5%), juvenile delinquency such as drinking alcohol, fights between groups/individuals, free sex and theft. Mawar Youth Integrated Service Post activities currently provide health check services and occasionally provide education about adolescent health, but do not yet have structured activity programs. It hasn’t had a youth cadre; the cadres are still affiliated with Toddlers and School-aged Integrated Service Post. This activity was aimed to increase teenagers' knowledge and understanding about reproductive health and prevention of early pregnancy; increasing access to information & getting interesting and interactive education; Helping teenagers make the right decisions about reproductive health; preventing early pregnancy, improving maternal and child health; The realization of quality and comprehensive services.  The active participation of teenagers in discussions shows changes in attitudes and increased commitment to reproductive health and prevention of early pregnancy. Post-activity questionnaire evaluation showed an increase of 12.3% in understanding reproductive health and prevention of early pregnancy for teenagers.